THE NATURE OF LAW IN PERSPECTIVE COMPARATIVE LAW - Harmono, Harmono (ANAYASA : Journal of Legal Studies, 2024)
Understanding the legal system as a complete unit, including institutions, procedures, and legal rules, where one element or sub-system has a relationship with other sub-systems. Law as a system has complexity and multiple perspectives, both the law in our own country, such as customary law, Islamic law, and our positive law, as well as western law, such as common law and the civil law system. We can see this complexity and multi-perspective, for example, in Islamic law, which considers religion and law to be one. Meanwhile, the Western legal system, especially in mainland Europe, is carried out through the formation of codification, in contrast to customary law, whose legal identity grows with the identity of the community that forms it, while positive law or national law in our country, Indonesia, which cannot be denied, still uses most of the written law that comes from "inheritance."" invaders. However, the differences in legal systems essentially mean that law always leads to the realization of justice, order, and order in society.